Tendinopathy and Aging: A Review of Literature and Considerations for Older Adult Athletes. Issue 1 (January 2016) - Jonely, Holly; Jayaseelan, Dhinu J.; Rieke, Meaghan
Abstract : Older adult athletes are prone to tendinopathies due to age-related tendon changes. Nonsteroidal anti-inflammatory drugs and corticosteroid injections have proven ineffective in managing chronic tendinopathies over the long term. Extracorporeal shockwave therapy and platelet-rich plasma injections may be effective in managing late-phase tendinopathy. Eccentric strength training is helpful for managing a variety of tendinopathies. Other effective programs include the Silbernagel combined program, whole body vibration, heavy slow resistance training, and stretching. Deep friction massage, modalities, joint mobilizations, and dry needling can be used in conjunction with exercise. Further research is needed to determine optimal intervention parameters for older adult athletes.